Engineering Mammalian Muscle Satellite Cells to Produce Viral Antigens - Skeens, Jordan. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Qiaobing Xu, and Nikhil Nair.; Keywords: Biomedical engineering, Immunology, and Food science.